The role of peptide hormones (adiponectin, leptin, insulin) in the pathogenesis of atherosclerosis - S. A. Smetnev; A. N. Meshkov (Столичная издательская компания, 2015)
Currently, cardiovascular diseases (CVD) remain the main problem in the world and in Russia in particular. The study of the causes and progression of atherosclerosis is a critical moment in the fight against CVD. Adipose tissue and processes that occur in it attracts attention in recent years. The important role of adipose tissue as an endocrine and immune organ is revealed as well as its participation in the development of the inflammatory process. This leads to the development of initial manifestations of atherosclerosis a precursor of many metabolic disorders and CVD. Particular attention causes adipokines regulatory peptide hormones in the adipose tissue, as well as insulin, due to its close relationship with the adipose tissue and especially with adiponectin and leptin. Recent data on the role of adiponectin, leptin and insulin in the pathogenesis of atherosclerosis in order to identify new potential targets among peptide hormones for the treatment of atherosclerosis are presented.